Chemical Composition and Larvicidal Activity of Lavandula angustifolia Subsp. angustifolia and Lavandula dentata Spp. dentata Essential Oils against Culex pipiens Larvae, Vector of West Nile Virus - Fouad El-Akhal; Amal Ramzi; Abdellah Farah; Yassine Ez Zoubi; Moussa Benboubker; Khalid Taghzouti; Abdelhakim El Ouali Lalami (Psyche: A Journal of Entomology)
The Culex pipiens mosquito (Diptera: Culicidae) is highly suspected to be the vector responsible for the spread of several parasitic and viral diseases. The use of synthetic insecticides is generally the preferred method of controlling these mosquitoes’ proliferation. However, it has led to resistance problems in target mosquitoes and environmental damage. Hence, diverse plant extracts could be considered as an alternative and potential source as mosquito control agents. In this study, essential oils of Lavandula angustifolia subsp. angustifolia and Lavandula dentata spp. dentata that are growing in Morocco were examined for their insecticidal effects on Culex pipiens larvae. The bioassay was performed according to a methodology inspired by the standard protocol of the World Health Organization. The mortality rate was determined after 24 hours of exposure, and probit regression analysis was used to calculate LC50 and LC90. The chemical analysis revealed that the principal compounds of L. angustifolia subsp. essential oils include linalool, linalyl acetate, geraniol, lavandulyl acetate, camphor, β-caryophyllene, terpinen-4-ol, β-myrcene, and 1,8-cineole, while the essential oil of L. dentata spp. was mainly composed of 1,8-cineole, camphor, α-pinene, trans-pinocarveol, linalool, and borneol. These volatile compounds have shown a toxic effect against Culex pipiens larvae, with lethal concentrations LC50 and LC90 being, respectively, 140 µg/ml and 450 µg/ml, for the L. angustifolia subsp. essential oil. Meanwhile, they were estimated at 2670 µg/ml and 7400 µg/ml, respectively, for the L. dentata spp. essential oil. These results suggest using essential oils of two species of Lavandula to control the Culex pipiens mosquito. It could be useful for the study of new natural larvicidal compounds.